Taxonomic remarks on Andraca Walker, 1865 (Lepidoptera: Bombycidae) with descriptions of five new species - Zolotuhin, Vadim V. (Zootaxa, 2012)
The genus Andraca Walker, 1865, is divided into two subgenera, one of them new: Chrypathemola Zolt., subgen. nov. (typespecies Andraca apodecta Swinhoe, 1907). The following new species are described: Andraca draco, sp. nov. (from Java);Andraca lawa, sp. nov. (from Palawan), Andraca paradisea, sp. nov. (from Philippines), Andraca chrysocollis, sp. nov. (fromPhilippines) and Andraca (Chrypathemola) nobilorum, sp. nov. (from Vietnam). A male lectotype for Andraca bipunctataWalker, 1865 is designated from the collection of ZMHU; this designation led to the new synonymy: Andraca bipunctata Walker, 1865 = Andraca angulata Kishida, 1993, syn. nov. The systematics of the family Bombycidae is briefly discussed.